2019
DOI: 10.1109/tpds.2018.2870651
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis and Modeling of Video Transcoding Using Heterogeneous Cloud Services

Abstract: High-quality video streaming, either in form of Video-On-Demand (VOD) or live streaming, usually requires converting (i.e., transcoding) video streams to match the characteristics of viewers' devices (e.g., in terms of spatial resolution or supported formats). Considering the computational cost of the transcoding operation and the surge in video streaming demands, Streaming Service Providers (SSPs) are becoming reliant on cloud services to guarantee Quality of Service (QoS) of streaming for their viewers. Clou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 46 publications
0
52
0
Order By: Relevance
“…in HC systems, namely uncertainty in tasks' execution times and uncertainty in tasks' arrival rate [17], [18].…”
Section: Defer Dropmentioning
confidence: 99%
See 1 more Smart Citation
“…in HC systems, namely uncertainty in tasks' execution times and uncertainty in tasks' arrival rate [17], [18].…”
Section: Defer Dropmentioning
confidence: 99%
“…Users issue independent service requests (termed tasks) from a set of offered service types (termed task-types). A task in our study is modeled as an independent video segment in the form of Group Of Pictures (GOPs) that is sequentially processed (e.g., transcoded [17]) within a deadline constraint. Each task has an individual hard deadline, which is the presentation time of that video segment [15], [25].…”
Section: Defer Dropmentioning
confidence: 99%
“…This distribution is obtained from historical execution times of a particular processing type (e.g., bit-rate transcoding) for a segment. It has been shown that the processing time of a video segment exhibits a normal distribution [8]. Let N E i (µ i j , σ i j ) be the probability distribution of completing the processing of segment i on FDN j; also let N T i (µ jv , σ jv ) be a normal distribution representing latency to deliver segment i from the local FDN j to the viewer's device v. Then, the probability distribution of delivering segment i to the viewer is calculated by convolving the two distributions as shown in Equation 2.…”
Section: B Robust Video Segment Delivery In F-fdnmentioning
confidence: 99%
“…In addition, caching on CDNs is less effective because of the fact that streaming providers have to maintain multiple versions of the same video to be able to support heterogeneous display devices and network conditions [6]. As such, instead of preprocessing video streams into multiple versions, mechanisms for on-demand processing (e.g., on-demand transcoding [6]) of video streams is becoming prevalent [7], [8]. However, the challenge is that on-demand video processing cannot be performed on CDNs since they are predominantly used for caching purposes [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation